Associations between dietary intake, physical activity, and obesity among public school teachers in Jeddah, Saudi Arabia - Almoraie, Noha M.; Shatwan, Israa M.; Althaiban, Maha A.; Hanbazaza, Mahitab A.; Wazzan, Huda A.; Aljefree, Najlaa M. (Frontiers in Nutrition, 2023)
Objective: we aimed to assess the dietary intake of certain food groups in a representative sample of public-school teachers living in Jeddah city. We also, examined the association of dietary intake with physical activity and obesity among schoolteachers. Methods: The study was a cross-sectional online survey, conducted among 640 (177 male, 463 female) schoolteachers aged between 20 and 62 years old and working in public primary, intermediate, and high schools in Jeddah. Measurements included gender, weight, height, body mass index (BMI), health problems, and lifestyle behaviours, including physical activity levels, smoking status, and dietary intake. Results: Based on gender, number of non-smoking women (94%) was higher than number of non-smoking men (57.1%) (P<0.001). However, men were more active than women (P=0.03). Regarding BMI, there were more overweight men than women, while obese women numbered more than men (P=0.003). There was no significant difference in dietary intake between men and women except that men consumed more soft drinks than women (P=0.002). Lower physically active schoolteachers were less likely to consume salad (OR=0.6, 95% CI 0.4–0.9; P=0.02), vegetables (OR=0.6, 95% CI 0.3–0.9; P=0.01), beans and legumes (OR=0.4, 95% CI 0.2–0.7; P=0.005), wholegrain bread (OR=0.6, 95% CI 0.4–0.9; P=0.03), dairy products (OR=0.6, 95% CI 0.4–0.9; P=0.01), snacks (OR=0.5, 95% CI 0.2–0.8; P=0.01), and fish (OR=0.4, 95% CI 0.2–0.9; P=0.04) compared to those with high levels of physical activity. Only fruit intake was considered statistically significant (OR=0.4, 95% CI 0.3–0.7; P=0.003). The study found a relationship between the BMI of schoolteachers and food intake. Obese schoolteachers had lower consumption of fruits (OR=0.3, 95% CI 0.2–0.7; P=0.007) and white meat (OR=0.5, 95%CI 0.3–0.9; P=0.03) than schoolteachers in the normal weight group. Conclusion: The high prevalence of physical activity, dietary intake and body weight among Saudi teachers is a major public health concern. The present study identified several lifestyle factors associated with body weight that may represent valid targets for the prevention and management of obesity among Saudi school teachers. Promoting active lifestyles and healthy diets would be primary targets for obesity prevention.